2012
DOI: 10.1266/ggs.87.299
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from principal component analysis for improvement of grain shape- and spikelet morphology-related traits after hexaploid wheat speciation

Abstract: Grain shape and size are involved in the main components of the domestication syndrome in cereals. Wheat grain shape has been dramatically altered at each stage of the domestication of tetraploid wheat and through common wheat speciation. To elucidate the evolutionary change of wheat grain shape, principal component (PC) analysis of grain shape-related traits was first conducted using wild and cultivated tetraploid, synthetic hexaploid, and common wheat accessions. The synthetic hexaploid wheat lines were prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 45 publications
2
35
2
Order By: Relevance
“…On the other hand, when Ldn was used as the single AB donor parent for production of synthetic wheat, D-genome variation for some morphological and physiological traits including flowering-related traits in Ae. tauschii was at least partly expressed in the hexaploid background (Kajimura et al, 2011;Okamoto et al, 2012). In the present study, QTL analyses revealed only two chromosomal regions controlling flowering-related traits in each mapping population, and failed to find any QTL previously identified using mapping populations of the synthetic hexaploid wheat lines.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, when Ldn was used as the single AB donor parent for production of synthetic wheat, D-genome variation for some morphological and physiological traits including flowering-related traits in Ae. tauschii was at least partly expressed in the hexaploid background (Kajimura et al, 2011;Okamoto et al, 2012). In the present study, QTL analyses revealed only two chromosomal regions controlling flowering-related traits in each mapping population, and failed to find any QTL previously identified using mapping populations of the synthetic hexaploid wheat lines.…”
Section: Discussioncontrasting
confidence: 93%
“…tauschii to common wheat through synthetic hexaploids (Kerber, 1987;Ma et al, 1995;Mujeeb-Kazi et al, 1996). Our empirical studies using a series of wheat synthetics have also shown enriched diversity of the D genome for some morphological and physiological characters (Takumi et al, 2009;Kajimura et al, 2011;Okamoto et al, 2012). The wide variation in HT observed among Ae.…”
Section: Introductionmentioning
confidence: 76%
“…WE6 and TE6 are EST-derived STS markers that are linked to Iw2 in two mapping populations [7,9]. In three of our mapping populations, linkage of the non-glaucousness loci to WE6 and TE6 were confirmed.…”
Section: Resultssupporting
confidence: 52%
“…In common wheat ( Triticum aestivum L., 2n = 6x = 42, genome constitution BBAADD), dominant alleles W1 and W2 , control the wax production and have been assigned to chromosomes 2B and 2D, respectively [5,6]. Additionally, dominant homoeoalleles for non-glaucousness, Iw1 and Iw2 , have also been mapped to the short arms of chromosomes 2B and 2D, respectively [6-9]. Wheat plants with either the w1, w2 , Iw1 or Iw2 allele show the non-glaucous phenotype, indicating that W1 and W2 are functionally redundant for the glaucous phenotype and that a single Iw dominant allele is sufficient to inhibit the glaucous phenotype even in the presence of a W1 or W2 allele [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Dubey et al (2006), using 45 morphometric features and ANN, correctly identified from 84% to 94% of the analysed wheat cultivars. The possibility of wheat cultivar discrimination / classification is the result of the inheritance of genes related to dimension and shape (Bergman et al, 2000;Okamoto et al, 2012), colour (Himi, Noda, 2005;Ficco et al, 2014) and endosperm hardness (Morris, Beecher, 2012), which accounts for the inter-cultivar differentiation. However, it is well known that these kernel features are highly affected by the conditions of plant vegetation, with the main impact being climate and fertilization regimes (Li et al, 2012;Lukow et al, 2012).…”
mentioning
confidence: 99%